Implementation of the Cambridge Curriculum in Physics Learning Management in SIS Semarang - Alhusni, Hanan Zaki; Suliyanah, Suliyanah; Deta, Utama Alan (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2024)
The curriculum is the backbone of education in every school. At the time of implementing the PLP in Semarang, the curriculum used at Secondary 3 (Junior High School class 9) to Junior College 2 (Senior High School class 3) in physics was Cambridge. The Cambridge Curriculum is an educational curriculum that gives students the skills they need for life, helping them achieve at school, university and work. This article aims to analyze the Cambridge curriculum in physics subjects at SIS Semarang. The method used in preparing the report on the results of the analysis was using interviews and direct observation at SIS Semarang. The school gives physics teacher the opportunity to develop learning styles, but demands that the syllabus must be discussed thoroughly, then the school also asks teachers to use active learning techniques, namely there is two-way interaction, such as students asking questions about the physics material, discussing it so that teacher can find out the students' abilities in the material. The school evaluates the implementation of the curriculum in the school which is always held every semester. There are several obstacles that may be faced in implementing the Cambridge curriculum, especially in physics subjects at SIS Semarang. Some of them are teacher readiness, required resources, student understanding, curriculum readiness to the local environment, and evaluation and assessment.